2019
DOI: 10.1002/cncr.32179
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase 3 trial comparing nimotuzumab plus cisplatin chemoradiotherapy versus cisplatin chemoradiotherapy alone in locally advanced head and neck cancer

Abstract: BACKGROUND:Because the addition of nimotuzumab to chemoradiation in patients with locally advanced head and neck cancer improved outcomes in a phase 2 study, the authors conducted a phase 3 study to confirm these findings. METHODS: This openlabel, investigator-initiated, phase 3, randomized trial was conducted from 2012 to 2018. Adult patients with locally advanced head and neck cancer who were fit for radical chemoradiation were randomized 1:1 to receive either radical radiotherapy (66-70 grays) with concurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(134 citation statements)
references
References 46 publications
5
89
0
1
Order By: Relevance
“… 19 A randomized phase III trial compared NTZ plus cisplatin and RT versus cisplatin and RT in locally advanced HNSCC, and also showed that the addition of NTZ improved PFS, LRC, DFS, and had a trend toward improved OS. 20 Both studies mentioned previously revealed that CTX or NTZ adds additional anti-tumor efficacy, thereby resulting in improved efficacy, which is similar to our findings. NTZ is biologically and molecularly different from CTX, 21 although they have similar mechanisms, NTZ inhibits both ligand-dependent and ligand-independent signaling of the EGFR pathway.…”
Section: Discussionsupporting
confidence: 92%
“… 19 A randomized phase III trial compared NTZ plus cisplatin and RT versus cisplatin and RT in locally advanced HNSCC, and also showed that the addition of NTZ improved PFS, LRC, DFS, and had a trend toward improved OS. 20 Both studies mentioned previously revealed that CTX or NTZ adds additional anti-tumor efficacy, thereby resulting in improved efficacy, which is similar to our findings. NTZ is biologically and molecularly different from CTX, 21 although they have similar mechanisms, NTZ inhibits both ligand-dependent and ligand-independent signaling of the EGFR pathway.…”
Section: Discussionsupporting
confidence: 92%
“…Addition of nimotuzumab as a radiosensitizer to weekly cisplatin and addition of cetuximab to carboplatin 5-FU resulted in an improvement in outcomes over weekly cisplatin and carboplatin-5 FU in locally advanced head and neck cancers [7,9]. However, a similar study of the addition of cetuximab to 3 weekly cisplatin was associated with negative results [8].…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol was approved by the institutional ethics committee and the study was conducted in accordance with national (Indian Council of Medical Research) and international guidelines (Good Clinical Practice and Declaration of Helsinki) on human research. The detailed inclusion-exclusion criteria with study protocol are already published [7]. The study enrolled patients with locally advanced head and neck cancer who were planned for curative intent therapy, had normal organ functions, no uncontrolled comorbidities and ECOG PS 0-2.…”
Section: Patient Population and Design Of The Studymentioning
confidence: 99%
See 2 more Smart Citations